Epidemiological profile of suicide cases in the Municipality of Campina Grande, Estado da Paraíba, Brazil (Research, Society and Development, 2020)
Objective: to investigate the epidemiological profile of suicide cases in the city of Campina Grande - PB. Method: this is a documentary, quantitative, descriptive study. The site of the research was the Campina Grande Health Secretariat - PB, in compulsory reporting forms of suicide cases that occurred between 2014 and 2018. This study received institutional authorization and approval from the CESED Research Ethics Committee, respecting the ethical principles of resolution 466/2012, CAAE: 19601619.4.0000.5175. Results: according to data provided by the Department of Health, it was observed that the highest number of deaths from suicide was among males (60; 68.2%), mixed race (74; 84.1%), aged 30 to 39 years (22; 25.0%), with a higher incidence of hanging / strangulation / suffocation (48; 54.5%) and having the domicile as the most prevalent place of occurrence (48; 54.5%). Noting that in 2018 was the year that had the highest mortality rate due to suicide (26; 29.5%). Conclusion: the data highlight the importance of acting preventively in populations with higher incidence of cases, as well as the need for appropriate approach and management to try to identify patients who have a profile of suicidal ideations for possible increasingly effective interventions.